An organic–inorganic hybrid birefringent material with diverse functional groups. Issue 54 (15th June 2021) - Chen, Yangxin; Zhu, Tingting; Xiong, Zheyao; Zhou, Yang; Li, Yanqiang; Ding, Qingran; Liu, Youchao; Chen, Xin; Zhao, Sangen; Luo, Junhua
Abstract : A synergistic effect of diverse functional groups leads to an organic–inorganic hybrid birefringent material (CN4 H7 )SbC2 O4 F2 (H2 O)0.5, which exhibits a birefringent response (Δ n = 0.126@546 nm) that is almost equal to that of the famous α-BaB2 O4 . Abstract : Birefringent materials are vital materials to modulate the polarization of light, and play a key role in plorization devices such as linear optical devices, optical communication devices, and fiber optic sensors. It is still a challenge to design excellent birefringent materials. Herein, we report an organic–inorganic hybrid oxalate birefringent material, (CN4 H7 )SbC2 O4 F2 (H2 O)0.5, by introducing organic delocalized π-conjugated [CN4 H7 ] + and [C2 O4 ] 2− groups, and stereochemical active inorganic SbO4 F2 polyhedra. (CN4 H7 )SbC2 O4 F2 (H2 O)0.5 exhibits a large birefringence (Δ n = 0.126@546 nm) that is almost equal to that of the well-known birefringent material α-BaB2 O4 . Theoretical calculations reveal that the distinguished birefringence should stem from the synergistic arrangement of π-conjugated [CN4 H7 ] + and [C2 O4 ] 2− planar groups, and highly distorted SbO4 F2 polyhedra with a stereochemically active lone pair. The synergistic effect of π-conjugated systems and the lone pair electrons greatly boosts the birefringence, which is helpful for the development of high-performance birefringent materials.